2017
DOI: 10.1007/s10396-017-0803-8
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave velocity measurement of upper trapezius muscle by color Doppler shear wave imaging

Abstract: This result suggests that our technique is satisfactorily reliable and has potential for future application in various fields, such as evaluation of muscle condition or the effects of rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This study confirmed good to excellent intra-session repeatability and moderate inter-rater and inter-session reproducibility for assessment of muscle stiffness, quantified by shear modulus values obtained with SWE imaging method. Several previous studies have reported similar findings for the trapezius muscle [6][7][8][9], however, within-participant typical errors were rarely reported [6]. In a study by Xie et al [6] very similar intra-session typical errors were found compared to the present study (CV = 6-8%) for trapezius shear modulus in resting position.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This study confirmed good to excellent intra-session repeatability and moderate inter-rater and inter-session reproducibility for assessment of muscle stiffness, quantified by shear modulus values obtained with SWE imaging method. Several previous studies have reported similar findings for the trapezius muscle [6][7][8][9], however, within-participant typical errors were rarely reported [6]. In a study by Xie et al [6] very similar intra-session typical errors were found compared to the present study (CV = 6-8%) for trapezius shear modulus in resting position.…”
Section: Discussionsupporting
confidence: 83%
“…The validity was confirmed throughout the full normal range of tension for appendicular skeletal muscle [13]. The reliability of the SWE for assessing muscle stiffness has been shown to be good or excellent for several muscle groups, including lower limb [5,11,12,14], trunk [4,10] and upper limb muscles [3,[6][7][8][9]. It has been suggested that SWE could also be used to monitor muscle activity [9,12,15,16].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Firstly, it may be the rst study to quantitatively assess MD elasticity by measuring the SWV at different shoulder abduction in healthy individuals. As a new tool to study muscle elasticity, most researches on SWE are almost about the Young's modulus [15,33]. Nevertheless, our studies had been done about the SWV.…”
Section: Discussionmentioning
confidence: 98%